Selected readings on community development - Chawdhari, T.P.S. (ed.) (Hyderabad, 1967)
AT the beginning of 1966, the National Institute of Community Development decided to bring together in a single volume important aspects of diffusion of agricultural innovations among the farming community in our country. At the time, it was felt that, out of the body of knowledge already accumulated, some chapters relating to particular aspects could be presented under the overall caption "Diffusion of Agri cultural Innovations". When we began to explore for the knowledge that had been gathered and to locate authors who could be approached to present an account of works done personally by them in this connection it was felt that while certain questions had been explored fairly often, there were others where not enough work seemed to have been done. As a result, the original plan had to be somewhat modified and with the materials furnished by the authors contacted in 1966, a modified volume under the caption Selected Readings on Community Development is now before the reader.
Keywords: Community development